Comparison of hematological parameters of venous and capillary blood in athletes - Podgórski, Tomasz; Bartkowiak, Urszula; Pawlak, Maciej (Akademia Wychowania Fizycznego w Poznaniu)
Objectives. Capillary blood sampling is less invasive than venous blood sampling; it is also often used in diagnosis of athletes. The hematological parameters are useful for general health assessment and adaptation of the athlete’s body to physical activity. Methods. The study was carried out on 40 healthy athletes (21 females and 19 males). Resting venous and capillary blood were obtained by fingerstick and collected to adequate tubes containing K2-EDTA as an anticoagulant. Blood analysis was performed using an 18-parametric hematology analyzer. The obtained measurement results were then compared. Blood cell count and hemoglobin concentration measurements involved the hematocrit correction formula which takes into consideration differences of plasma volumes in tested tubes. Results. The obtained results show that differences between hematological indicators were not statistically significant except for the mean corpuscular volume (MCV; p < 0.05), which was lower, and the mean platelet volume (MPV; p < 0.001), which was higher in the capillary blood, respectively. The involvement of hematocrit correction formula showed a lower granulocytes count (p < 0.05) and platelet count (p < 0.01) in the capillary blood. Differences between the indices ranged from 0.04 to 3.79 percent. Conclusions. The obtained hematological parameters of venous and capillary blood show comparable values. Assessment of athletes’ health can be based on an analysis of hematological parameters using a less invasive method of capillary blood sampling
Keywords: erythrocyte count; leukocyte count; thrombocytecount; leukocyte subpopulations; hematocrit index; differencesof the hematocrit value; blood collecting